Accumulation of perfluoroalkyl substances in lysimeter-grown rice in Japan using tap water and simulated contaminated water. (September 2019) - Yamazaki, Eriko; Taniyasu, Sachi; Noborio, Kosuke; Eun, Heesoo; Thaker, Pooja; Kumar, Nirmal J.I.; Wang, Xinhong; Yamashita, Nobuyoshi
Abstract: Perfluoroalkyl substances (PFASs) are a group of contaminants of concern in agricultural crops, but little is known of their accumulation or behavior in grains. We grew Japanese rice ( Oryza sativa subsp. indica ) in lysimeters irrigated with tap water or tap water plus simulated contaminated water for 2 years, then analyzed the roots, straw, unhulled rice, white rice, bran, soil, and water for PFASs residues. Total fluorine was measured by combustion ion chromatography. Estimated per-plant residue levels were 3.0 pg perfluorooctanesulfonic acid (PFOS) (bran: 0.5%, hull: 99.5%), 0.54 pg N -ethylperfluorooctanesulfonamide ( N -EtFOSA) (white rice: 67%, hull: 33%), 1.2 pg perfluorobutanoic acid (PFBA) (white rice: 13%, bran: 7%, hull: 79%), 0.68 pg perfluoropentanoic acid (hull: 100%), 0.50 pg perfluorohexanoic acid (PFHxA) (white rice: 65%, bran: 16%, hull: 19%), 0.21 pg perfluoroheptanoic acid (hull: 100%), 0.25 pg perfluorooctanoic acid (PFOA) (hull: 100%), and 0.12 pg perfluorodecanoic acid (PFNA) (white rice: 81%, bran: 19%). Estimated daily PFASs intakes were <1–3 ng perfluorooctanesulfonamide, <1–7 ng N-EtFOSA, 1–2 ng PFBA, <3–4 ng PFHxA, and 1–2 ng PFNA. Estimated PFOS, PFOA, and total PFASs in straw feed were 0.4, 0.1, and 2 kg yr −1 and 0.7, 0.4, and 8 kg yr −1 in 2015 and 2016, respectively. Estimated PFOS, PFOA, and total PFASs in straw fertilizer were 4, 1, and 23 kg yr −1 and 7, 4, and 86 kg yr −1 in 2015 and 2016, respectively. PFASs accumulation may cause longer residence time in agricultural systems owing to straw being used as animal feed and organic fertilizer. Graphical abstract: Image 1 Highlights: Lysimeter-grown rice was irrigated with tap water alone or added contamination. PFASs were analyzed for rice plant. PFOS and PFOA were not detected in white rice. PFASs were accumulated in unhulled rice, rice bran, straw and roots. FOSA had the highest transfer factor from soil to rice, similar to N and P.